Pengaruh Kualitas Pelayanan dan Suasana Toko Terhadap Keputusan Pembelian Pada April Eyewear Jakarta - Fachri Aditya; Taufik Akbar (Administratif Profesional, 2023)
The purpose of this study was to analyze whether there is an influence between service quality and store atmosphere variables on purchasing decisions for April Eyewear. This research is expected to be an evaluation and consideration material for April Eyewear to improve service quality and store atmosphere, thereby increasing consumer purchasing decisions. This study uses a quantitative approach to the technique of determining the sample using the accidental sampling method. The number of samples taken was 87 respondents. Instrument testing uses validity and reliability tests. The data analysis method used is multiple linear regression, coefficient of determination test (R Square), T test, and F test. Data processing in this study was carried out using SPSS 16 software for windows. Based on the results of R Square, 74.6% of service quality variables (X1) and store atmosphere (X2) influence purchasing decisions (Y) while the remaining 25.4% is explained by other factors that are not included in this research model.